Limnospira indica PCC 8005 Supplementation Prevents Pelvic Irradiation-Induced Dysbiosis but Not Acute Inflammation in Mice - Charlotte Segers; Mohamed Mysara; Amelie Coolkens; Shari Wouters; Sarah Baatout; Natalie Leys; Sarah Lebeer; Mieke Verslegers; Felice Mastroleo (MDPI AG, 2023)
Pelvic irradiation-induced mucositis secondarily leads to dysbiosis, which seriously affects patients' quality of life after treatment. No safe and effective radioprotector or mitigator has yet been approved for clinical therapy. Here, we investigated the potential protective effects of fresh biomass of Limnospira indica PCC 8005 against ionizing irradiation-induced mucositis and dysbiosis in respect to benchmark probiotic Lacticaseibacillus rhamnosus GG ATCC 53103. For this, mice were supplemented daily before and after 12 Gy X-irradiation of the pelvis. Upon sacrifice, food supplements' efficacy was assessed for intestinal barrier protection, immunomodulation and changes in the microbiota composition. While both could not confer barrier protection or significant immunomodulatory effects, 16S microbial profiling revealed that L. indica PCC 8005 and L. rhamnosus GG could prevent pelvic irradiation-induced dysbiosis. Altogether, our data show that-besides benchmarked L. rhamnosus GG-L. indica PCC 8005 is an interesting candidate to further explore as a radiomitigator counteracting pelvic irradiation-induced dysbiosis in the presented in vivo irradiation-gut-microbiota platform.